External energy sources in body contouring - Denis Souto Valente; Michel Pavelecini (Revista Brasileira de Cirurgia Plástica)
During the 39th South Brazilian Plastic Surgery Conference, in April 2024, a heated debate arose regarding the promotion of the use of technologies for body contouring surgery on social media. An important question was raised: are they being prematurely promoted on social media before being rigorously evaluated? The quote from Dr. Ian Malcolm, a famous creation of Michael Chrichton, “I’ll tell you the problem with the power you’re using here, it didn’t require any discipline to attain it” applies perfectly to this situation. Promoting techniques on social media should require the same rigorous discipline as scientific research. The absence of research protocols approved by the National Research Ethics Council and high-level evidence publications in peer-reviewed journals raises concerns. The power to enhance our results using these external energy sources is real, and its use represents a significant advancement within plastic surgery. However, it is imperative that plastic surgeons exercise caution when promoting new technologies. Scientific discipline should be the foundation of any advancement, and responsible disclosure should precede popularization. Only then can we ensure that patients benefit from safe and effective treatments without compromising the integrity of our specialty.